Efficacy and Safety of Low Flow Oxygen During Procedural Sedation in the Office; An Analysis of SAO2 (pulse oximetry) and End Tidal Expired Oxygen(FeO2). - Melloni, Claudio (British Journal of Healthcare and Medical Research, 2024)
Purpose: measurement of FeO2 confirms the safety of low flow oxygen. Patients and methods: In a series of 235 patients undergoing office plastic and dental surgery under conscious sedation with midazolam/fentanyl or promazine/meperidine during the Covid pandemia we evaluated the safety of low flow (0.5-1 lt/min) oxygen adding the continuous measurement of FeO2 to the standard non invasive monitoring. Results: FeO2 demonstrated no relationship with pulse oxymetry and a negative relationship with etCO2.Low flow oxygen corrected both FeO2 and SaO2.Vital signs were stable and all patients were discharged home within 2 hr after surgery. Conclusion :FeO2 measurement could constitute an early warning signal of impendind danger and serve the purpose of oxygen sparin